APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Mineral Resources Potential in Mozambique - Lehto, Tapio; Gonçalves, Reinaldo (Geological Survey of Finland, 2008)
The metallic mineral, industrial mineral and construction material resources in Mozambique have been mapped as part of the Mineral Resources Management Capacity Building Project, financed by a grant provided by the Nordic Development Fund. A database covering the location and characteristics of more than 600 mineral indications, showings and deposits within the geographical contract area assigned to the GTK Consortium was created. A total of 140 mineral occurrences were selected for field surveys and assessments that were mainly carried out during May-November 2003, 2004 and 2005. All available data in the report archives of the client, the National Directorate of Geology (DNG), was collected and transferred to the mineral occurrence database, which was then updated with information from field surveys and with new data published by exploration and mining companies on the Internet. New mineral resources maps at the scales 1:50 000 (part of contract area), 1:250 000 and 1:1 million were prepared with the corresponding symbols for various commodities plotted. Favourability maps showing zones with high potential for selected commodities were compiled at the 1:250 000 scale. The mineral resources in Mozambique were described in the four map explanation volumes and summarized in the final reports for the projects Geological Mapping LOT 2 and Geological Mapping LOT 3. As a consequence of increased geological knowledge, facilitated by the activities of the GTK Consortium, investments in Mozambique’s mineral potential by leading international and regional mining companies is already increasing. Currently, global mining houses are investing in exploration for energy minerals (hydrocarbons, coal and uranium), for titanium and zirconium in heavy mineral sands, for gold and gemstones, for the agricultural minerals lime and phosphate and for tantalum, fluorite and other industrial minerals.
Keywords: G - Mozambique / Moçambique; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; ⛔ No DOI found

Exploring Natural Resources in Mozambique: Will it be a Blessing or a Curse? - Bacuane, Aurélio; Mulder, Peter (Instituto de Estudos Sociais e Económicos (IESE), 2007)
Mozambique has considerable quantity of natural resources, of which the major part is yet to be explored. The Government of Mozambique is determined to extract and export its natural resource potential as soon as possible, supposing that this will positively contribute to economic growth and poverty reduction. However, any resources rich countries are among the poorest nations in the world, in spite of decennia-long exploration of their natural wealth. This so colled 'paradox of plenty' or 'resource curse' raises the question whether the foreseen exploration of natural resources in Mozambique will pose a serious threat rather than a blessing to its economic development. In this paper we first estimate the potential resource wealth of Mozambique in comparison to other countries. Next, we briefly review the rowing body of literature on the existence and determinants of a natural resource curse. Then we evaluate the risk of a resource curse to occur in Mozambique in the (near) future. Finally, we try to come up with suggestions to avert a Mozambican resource curse.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; transparency / transparência